2019
DOI: 10.1101/841171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genome of the zoonotic malaria parasite Plasmodium simium reveals adaptations to host-switching

Abstract: Oxford, Headington, Oxford, OX3 9DU, UK 41 42 §) Contributed equally, arranged alphabetically 43 †) Corresponding authors 44 45 46 Summary 47 48 Plasmodium simium, a malaria parasite of non-human primates in the Atlantic forest region of 49Brazil was recently shown to cause zoonotic infection in humans in the region. Phylogenetic 50 analyses based on the whole genome sequences of six P. simium isolates infecting humans 51 and two isolates from brown howler monkeys revealed that P. simium is monophyletic within… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 96 publications
2
24
0
Order By: Relevance
“…brasilianum is identical to P. malariae, and P. simium to P. vivax [8]. This similarity has been confirmed by molecular studies, which showed a high identity between the genomes in each of these pairs of plasmodia [12][13][14][15], suggesting recent speciation and reinforcing the possibility of Plasmodium transmission from monkeys to humans and vice versa [15][16][17].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…brasilianum is identical to P. malariae, and P. simium to P. vivax [8]. This similarity has been confirmed by molecular studies, which showed a high identity between the genomes in each of these pairs of plasmodia [12][13][14][15], suggesting recent speciation and reinforcing the possibility of Plasmodium transmission from monkeys to humans and vice versa [15][16][17].…”
Section: Introductionmentioning
confidence: 57%
“…Howler monkeys (Alouatta clamitans) are probably the main reservoir of malarial parasites (P. simium / P. vivax) that cause zoonotic infections in humans in the Atlantic Forest [11]. Analysis of the P. simium genome revealed that these zoonotic parasites underwent host-switching adaptations, including switching (1) from European humans carrying P. vivax to New World monkeys during the first centuries of Brazilian colonization and (2) from New World monkeys carrying P. simium (a descendent form of P. vivax) to modern humans engaging in forest activities [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the same study also reported significant differences between P. vivax and P. simium in the genes encoding region 1 of the Duffy binding protein 1 (DBP1) and the reticulocyte binding protein 2 (RBP2a). The authors suggest that these changes in the key encoding erythrocyte invasion ligands together with other genetic changes possibly facilitated the transfer of P. simium to humans [ 44 ].…”
Section: Simian Plasmodia and Their Relationshimentioning
confidence: 99%
“…A majority of transcription take place during the schizont-ring transition [ 121 ], suggesting their role in erythrocyte invasion. The proportion of non-synonymous SNPs in PvTRAg genes was shown to be significantly high, suggesting the effect of diversifying selection related to antigenic function [ 122 ]. Nine PvTRAgs have been shown to bind to human erythrocytes, including PvTRAg33.5, PvTRAg35.2, PvTRAg69.4, PvTRAg34, PvTRAg38, PvTRAg36, PvTRAg74, PvTRAg26.3, and PvTRAg36.6.…”
Section: Plasmodium Vivax Ligand Proteins and Hmentioning
confidence: 99%